Dramatic resolution of an immediate postoperative distortion of the circumflex artery during mitral valve surgery. Issue 5 (1st April 2020) - Caruso, Vincenzo; Sabry, Haytham; Birdi, Inderpaul
Abstract: Injury or distortion of the circumflex coronary artery can occur during mitral valve surgery, due to its proximity to the mitral valve annulus. We present the case of a 72‐year‐old male patient with symptomatic mitral regurgitation, who underwent minimally invasive mitral valve surgery. The initial reparative gesture was complicated by intraoperative infarct due to a distortion of the circumflex artery (CX) caused by the rigidity of the ring used; the mainstay of the treatment was the removal of the previous device implanted in favor of a flexible one with restitutio ad integrum of the CX patency.